ANALISIS PENILAIAN KINERJA KEUANGAN MENGGUNAKAN PENERAPAN ECONOMIC VALUE ADDED (EVA) dan MARKET VALUE ADDED (MVA) PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015-2018 - Dewi Oktary (STIE 'INDONESIA' Pontianak, 2019)
This study aims to determine the assessment of financial performance using Economic Value Added (EVA) and Market Value Added (MVA) methods for telecommunications companies listed on IDX in the period 2015-2018. EVA is an estimate of the actual economic profit of business for particular year. MVA is the reduction between market value of equity and equity capital invested. The research method used is a quantitative descriptive method with a sampel of telecommunications companies listed on IDX, with secondary data collection techniques. The results of this study indicate that from 2015-2018 PT. TELKOM has positive EVA, In 2015-2016 BTEL has postive EVA value, while 2017-2018 EVA negative value. ISAT 2015-2016 EVA value is negative, 2017 EVA Value is positive, 2018 EVA value is negative. While In 2015 XL has EVA negative EVA value, In 2016-2017 EVA value is positive, and 2018 XL has EVA negative. For the MVA calculation form 2015-2018 PT. TELKOM and BTEL have positive MVA values, FREN has MVA negative. In 2015 ISAT MVA is negative. In 2016-2018 the value of MVA is positive. Whereas In 2015-2016 XL has negative MVA, In 2017-2018 MVA value is positive. It can be seen that although the EVA value is positive, the MVA value is not necessarily positiv